L’archipel des Antilles, terres d’Amérique ? : la nouvelle "New Frontier" et ses implications - Lionel Davidas (Anglophonia)
"America to the Americans." For years and years, that phrase conveying the spirit of the "Monroe doctrine" has been periodically evoked to justify the United States’ expansionist and interventionist designs in this region. But is the West Indian archipelago a mere outpost of continental America or a distinct entity that circumscribes what Édouard Glissant has named "The hurricane basin"? What might have prompted the USA to intervene so often in that zone since the Hispano-American war in 1898? Does the concept of "the manifest destiny" find a legitimate application in the Caribbean islands? And can the "Frontier" or "New Frontier" paradigms be useful operators that can guide our reflection? This paper will try and answer those significant questions.